Land Management with due Regard to Quasi-Rent - Yermolenko, Dmytro; Gryshko, Viktor; Chaikina, Alina; Buchniev, Maxym (International Journal of Engineering and Technology, 2018)
Methodological approach to calculating the differential rent of type â€œIâ€ according to spacing (allocation) of lands to market outlets has been offered in this article. In the result of research, we have ascertained that in transport rent formation there encounters another one, more concealed as for net profit type of rent â€“ quasi-rent. The contributors have also substantiated the factors that affect quasi-rental value and have determined the main dominant features, which allow identification of quasi-rent on land.Â Â